A template-confined fabrication of controllable gold nanoparticles based on the two-dimensional nanostructure of macrocycles. Issue 31 (19th March 2015) - Geng, Yanfang; Liu, Miaoqing; Xue, Jindong; Xu, Peng; Wang, Yifei; Shu, Lijin; Zeng, Qingdao; Wang, Chen
Abstract : An amine-substituted macrocycle6Y, a rigid hexagonal ring, self-assembled into a network architecture on the surface, which could be used as a molecular template to directly fabricate gold nanoparticles (AuNPs) with narrow size distribution (2.2 ± 0.1 nm). Abstract : An amine-substituted macrocycle6Y, a rigid hexagonal ring, self-assembled into network architecture on the surface, which could be used as a molecular template to directly fabricate gold nanoparticles (AuNPs) with narrow size distribution (2.2 ± 0.1 nm). This work demonstrated a new pathway for the formation of controllable AuNPs on the surface.